BARC resin, and preparation method and application thereof
By using an electrospinning device in a 193nm deep ultraviolet photoresist to remove small molecule impurities, the pattern resolution and edge roughness problems were solved, and higher photoresist accuracy and film thickness uniformity were achieved.
Patent Information
- Application Number
- CN202411412859.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
AI Technical Summary
The pattern resolution of the existing 193nm deep ultraviolet photoresist is not ideal, the edge roughness is high, and the molecular weight distribution of BARC resin is wide, resulting in a significant standing wave effect, affecting the processing accuracy of the photoresist.
Polymerization reaction of styrene monomer, acrylic monomer and initiator is carried out, spray droplets are formed using electrospinning device to remove small molecular impurities, and BARC resin with narrow molecular weight distribution is obtained, which is used in 193nm deep ultraviolet photoresist preparation.
The pattern resolution and edge roughness of 193nm deep ultraviolet photoresist are significantly improved, the film thickness uniformity is improved, the standing wave effect is reduced, and the processing accuracy of the photoresist is improved.
Smart Images

Figure CN119241755A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor technology, and in particular relates to a BARC resin, a preparation method and application thereof. Background Art
[0002] With the development of photoresist technology, the precision of micro-pattern processing size is constantly improving, and higher requirements are placed on the pattern resolution of photoresist. At this time, in addition to considering the performance of the photoresist resin itself, it is also necessary to consider the role of related components, such as the impact of the bottom substrate on the photoresist, including the adhesion of the bottom substrate and the photoresist, the uniformity of the bottom substrate, the absorption and reflection of the bottom substrate, etc. In order to obtain a finer pattern, it is necessary to reduce the exposure wavelength and the film thickness of the bottom substrate, but the thinner the film thickness, the stronger the penetration of the light source for the photoresist, and the reflection phenomenon formed is also strengthened. During the photolithography process, the reflected light will expose the photoresist twice or multiple times, that is, produce a standing wave effect, resulting in the inability to control the critical dimensions, increasing the difficulty of micro-pattern processing, especially when using inorganic substrate materials such as silicon, silicon nitride, and gallium nitride, the light reflection energy is strong and the standing wave effect is particularly obvious.
[0003] In order to eliminate the standing wave effect, a bottom anti-reflective coating (BARC) can be introduced. Organic BARC generally uses one or more organic polymers to obtain an anti-reflective coating with uniform thickness through spin coating, and uses the absorption of light by the dye group in the organic polymer to reduce reflection. When a benzene ring structure is introduced into the polymer used for BARC (i.e., BARC resin), it has a strong absorption capacity for 193nm light and is suitable for 193nm deep ultraviolet photoresist.
[0004] BARC resins with different molecular weights are suitable for anti-reflective coatings with different film thicknesses. The molecular weight and molecular weight distribution of BARC resins will affect the uniformity and anti-reflective effect of the anti-reflective coating, and thus affect the resolution of the photoresist pattern. At present, the resolution of the photolithography pattern of 193nm deep ultraviolet photoresist is not ideal, and there is a problem of high edge roughness (LWR). The molecular weight distribution of the existing BARC resins used in 193nm deep ultraviolet photoresists is also relatively wide, and the effect of improving the pattern resolution and LWR is not good. Summary of the invention
[0005] In view of the above problems, the present invention provides a BARC resin, a preparation method and uses. The BARC resin obtained by the preparation method is suitable for the preparation of 193nm deep ultraviolet photoresist, and has a narrow molecular weight distribution. The anti-reflective coating formed has good uniformity, which effectively improves the resolution and LWR of the 193nm deep ultraviolet photoresist pattern.
[0006] In one aspect of the present invention, a method for preparing a BARC resin is provided, the method comprising:
[0007] S1, placing styrene monomers and acrylic monomers in a reaction solvent and mixing them evenly to obtain a prepolymer solution;
[0008] S2, adding an initiator to the prepolymer liquid, heating it to boiling to carry out a free radical polymerization reaction, and obtaining a reaction liquid;
[0009] S3, adding the reaction liquid to the electrospinning device, and placing the needle outlet of the electrospinning device above the container filled with washing liquid; turning on the electrospinning device, pushing the reaction liquid, and when droplets appear on the needle, applying voltage to the needle to form a spray and enter the washing liquid, the small molecular substances in the spray are dissolved in the washing liquid, and the macromolecular substances form precipitation;
[0010] S4, separating the precipitate to obtain the BARC resin.
[0011] Another aspect of the present invention provides a BARC resin, which is prepared by the above-mentioned method for preparing the BARC resin.
[0012] Another aspect of the present invention provides the use of BARC resin in the preparation of 193nm deep ultraviolet photoresist.
[0013] Compared with the prior art, various aspects of the present application provide BARC resins, preparation methods and uses, which can achieve at least one of the following beneficial effects: a reaction liquid containing a macromolecular polymer is obtained by polymerization reaction of styrene monomers, acrylic monomers and initiators, and the reaction liquid is sprayed with an electrostatic spinning device to form fine droplets, which enter the washing liquid and can contact the washing liquid more fully, wherein small molecular impurities are dissolved by the washing liquid, and the macromolecular polymer forms a precipitate, and the precipitate is separated and dried to obtain a BARC resin with a narrower molecular weight distribution. The BARC resin of the present application contains a benzene ring structure and has a strong absorption capacity for 193nm light. At the same time, the BARC resin has a narrow molecular weight distribution, and the BARC formed by spin coating on a silicon wafer with a cross-linking agent has good uniformity and is used for the preparation of 193nm deep ultraviolet photoresist, which can effectively improve the resolution and LWR of the pattern. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The film thickness (FT) of the BARC resin corresponding to the photoresist in each example;
[0015] Figure 2 The film thickness uniformity (STDEV) of each example BARC resin corresponding to the photoresist when prepared;
[0016] Figure 3 The BARC resin of each example corresponds to the prepared 193 nm deep ultraviolet photoresist. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] When improving the resolution of photoresist, the prior art mostly considers changing the performance of the photoresist resin itself. For example, CN117659256A discloses a narrow distribution 193nm deep ultraviolet photoresist resin and its preparation method and application, wherein a resin monomer and a main initiator are dissolved in a solvent and undergo a free radical polymerization reaction under heating conditions, and a secondary initiator is added in the later stage of the reaction to promote a more uniform free radical polymerization reaction, thereby obtaining a narrow distribution 193nm deep ultraviolet photoresist resin. The present invention considers from a different perspective that the resolution of the photoresist is improved by improving the BARC resin to better eliminate the standing wave effect.
[0019] The embodiment of the present invention provides a method for preparing a BARC resin, the method comprising S1 to S4:
[0020] S1. Styrene monomers and acrylic monomers are placed in a reaction solvent and mixed evenly to obtain a prepolymer solution.
[0021] S2, adding an initiator to the prepolymer liquid, heating it to boiling to carry out a free radical polymerization reaction, and obtaining a reaction liquid;
[0022] S3, adding the reaction liquid to the electrospinning device, and placing the needle outlet of the electrospinning device above the container filled with washing liquid; turning on the electrospinning device, pushing the reaction liquid, and when droplets appear on the needle, applying voltage to the needle to form a spray and enter the washing liquid, the small molecular substances in the spray are dissolved in the washing liquid, and the macromolecular substances form precipitation;
[0023] S4, separating the precipitate to obtain the BARC resin.
[0024] In the prior art, the reaction liquid after the polymerization reaction is completed is directly added to the washing liquid for washing and precipitation, wherein a large number of small molecular impurities that have not reacted completely or are generated during the reaction process are easily wrapped in the macromolecular polymer and are difficult to remove, resulting in a wide molecular weight distribution of the finally obtained BARC resin. The present invention uses an electrostatic spinning device to atomize the reaction liquid, so that very fine droplets are formed and enter the washing liquid, and the small molecular impurities can fully contact the washing liquid, and the small molecular impurities wrapped by the macromolecular polymer are also exposed, so that the small molecular impurities are better dissolved and removed by the washing liquid, and a BARC resin with a narrower molecular weight distribution is obtained.
[0025] It should be noted that the photoresist resin of CN117659256A is prepared by polymerization of methacrylic monomers, and the BARC resin of the present invention is obtained by polymerization of ethylene monomers and acrylic monomers. The reaction systems of the two are different, the small molecule impurities are also different, and the difficulty of removal is also different. The method suitable for removing impurities from the photoresist resin may not be suitable for removing impurities from the BARC resin, and the effect is also unpredictable.
[0026] In some embodiments, the styrene monomer is at least one of p-hydroxystyrene and styrene; the acrylic monomer is at least one of methoxyethyl methacrylate and hydroxypropyl methacrylate.
[0027] In some embodiments, the reaction solvent is at least one of tetrahydrofuran, butanone, and propylene glycol methyl ether acetate.
[0028] In some embodiments, the styrene monomer is p-hydroxystyrene; the acrylic monomer is methoxyethyl methacrylate and hydroxypropyl methacrylate; the reaction solvent is tetrahydrofuran; and the weight ratio of p-hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate and tetrahydrofuran in the prepolymer solution is 1-10:1-10:1-10:12-120.
[0029] In some embodiments, the initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, and azobisisoheptanenitrile.
[0030] In some embodiments, the total amount of the styrene monomer and the acrylic monomer to the initiator is in a ratio of 10-100:0.06-0.6.
[0031] In some embodiments, the specification of the needle of the electrospinning device is 15G, the outer diameter is 1.8mm, the distance between the needle and the upper surface of the washing liquid is 15cm, the voltage applied to the needle ranges from 10 to 30kv, and the propulsion rate of the reaction liquid is 1mL / h. More preferably, the range of the applied voltage is 20 to 30kv, and more preferably 25 to 30kv. The parameter settings of the electrospinning device are obtained through a large number of experimental optimizations. Under these parameter settings, the best effect can be obtained, and small molecule impurities can be better removed. The test process unexpectedly found that as the voltage increases, the weight-average molecular weight of the BARC resin tends to increase, the molecular weight distribution tends to narrow significantly, and the minimum molecular weight tends to increase. Within a certain range, the ideal BARC resin can be obtained by controlling the voltage. For example, setting the voltage to 30kv can obtain a BARC resin with the narrowest molecular weight distribution, whose polymer dispersibility index is 1.33 and the molecular weight distribution is the narrowest, which is significantly better than the BARC resin obtained under other voltages.
[0032] In some embodiments, the washing liquid is at least one of isopropanol, n-heptane, n-hexane, and ethanol.
[0033] The embodiment of the present invention provides a BARC resin. Through the preparation method of the BARC resin of the present invention, the present invention prepares a BARC resin with a weight average molecular weight of about 20,000 and a narrow molecular weight distribution (PDI not exceeding 1.8).
[0034] The embodiment of the present invention provides the use of the BARC resin in the preparation of 193nm deep ultraviolet photoresist. Compared with the use of the existing BARC resin, the BARC resin of the present invention is used as the main component to perform film coating, and the film thickness uniformity is good. After performing 193nm deep ultraviolet lithography, the LWR of the obtained pattern is low and the resolution is higher, which is particularly suitable for the preparation of 193nm deep ultraviolet photoresist.
[0035] Example 1
[0036] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0037] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0038] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0039] S3. Cool the reaction liquid and transfer it to the electrospinning device. The needle has a specification of 15G and an outer diameter of 1.8mm. The distance between the needle and the upper surface of n-hexane (washing liquid) is 15cm. A voltage of 15KV is applied to the needle. The propulsion rate of the reaction liquid is set to 1mL / h for atomization. The fine droplets formed after the reaction liquid is atomized enter the n-hexane to form a precipitate. The amount of n-hexane used is 10 times that of the reaction liquid.
[0040] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0041] Example 2
[0042] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0043] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0044] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0045] S3, cool the reaction liquid, and transfer the reaction liquid to the electrospinning device. The specification of the needle is 15G, the outer diameter is 1.8mm, the distance between the needle and the upper surface of n-hexane (washing liquid) is 15cm, a voltage of 20KV is applied to the needle, the propulsion rate of the reaction liquid is set to 1mL / h, and atomization is performed. The fine droplets formed after the reaction liquid is atomized enter the n-hexane to form a precipitate. The amount of n-hexane used is 10 times that of the reaction liquid.
[0046] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0047] Example 3
[0048] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0049] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0050] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0051] S3, cool the reaction liquid, and transfer the reaction liquid to the electrospinning device. The specification of the needle is 15G, the outer diameter is 1.8mm, the distance between the needle and the upper surface of n-hexane (washing liquid) is 15cm, a voltage of 25KV is applied to the needle, the propulsion rate of the reaction liquid is set to 1mL / h, and atomization is performed. The fine droplets formed after the reaction liquid is atomized enter the n-hexane to form a precipitate. The amount of n-hexane used is 10 times that of the reaction liquid.
[0052] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0053] Example 4
[0054] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0055] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0056] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0057] S3, cool the reaction liquid, and transfer the reaction liquid to the electrospinning device. The specification of the needle is 15G, the outer diameter is 1.8mm, the distance between the needle and the upper surface of n-hexane (washing liquid) is 15cm, a voltage of 30KV is applied to the needle, the propulsion rate of the reaction liquid is set to 1mL / h, and atomization is performed. The fine droplets formed after the reaction liquid is atomized enter the n-hexane to form a precipitate. The amount of n-hexane used is 10 times that of the reaction liquid.
[0058] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0059] Comparative Example 1
[0060] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0061] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0062] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0063] S3. Cool the reaction solution and add n-hexane to precipitate the reaction solution; the amount of n-heptane used is 10 times that of the reaction solution.
[0064] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0065] Comparative Example 2
[0066] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0067] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0068] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0069] S3, cooling the reaction solution, and adding n-hexane to precipitate the reaction solution. The amount of n-heptane used is 15 times that of the reaction solution.
[0070] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0071] Comparative Example 3
[0072] p-Hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrofuran (reaction solvent) were taken in a weight ratio of 2:2:1:10, and azobisisobutyronitrile (initiator) was 0.3% of the total monomer amount (total weight of p-hydroxystyrene, methoxyethyl methacrylate, and hydroxypropyl methacrylate), and the BARC resin was prepared according to the following steps.
[0073] S1. Place p-hydroxystyrene, methoxyethyl methacrylate and hydroxypropyl methacrylate in a four-necked flask containing tetrahydrofuran, and stir until the monomers are evenly mixed.
[0074] S2. After the monomer is dissolved, add azobisisobutyronitrile and stir until dissolved. Place the four-necked flask containing the reaction solution in an oil bath equipped with a magnetic stirrer, install the condenser and nitrogen interface, open the condenser, and introduce nitrogen. Start stirring and heat until the solvent boils (about 65°C) to carry out free radical polymerization reaction, and the reaction time is 24 hours.
[0075] S3, cooling the reaction solution, and adding the reaction solution into n-hexane for precipitation. The amount of n-heptane used is 20 times that of the reaction solution.
[0076] S4, solid-liquid separation, taking out the precipitate, drying it, and weighing it to obtain BARC resin.
[0077] Comparative Study on the Performance of BARC Resins
[0078] The BARC resin in each example was tested for weight average molecular weight and molecular weight distribution by GPC method. The results are shown in the following table:
[0079] Table 1 Summary of some difference parameters and BARC resin test results of each example
[0080]
[0081] As can be seen from the above table, the PDI of the BARC resin of Examples 1-4 is significantly lower than that of Comparative Examples 1-3, and the minimum molecular weight is significantly larger, indicating that the BARC resin obtained in Examples 1-4 contains fewer small molecule impurities and a narrower molecular weight distribution. Further, by comparing the polymer precipitation steps of the examples and comparative examples, it can be seen that compared with adding the reaction solution directly to the washing liquid, the use of an electrospinning device to form the reaction solution into spray droplets and then enter the washing liquid can better remove small molecule impurities. This may be because the formation of a fine spray increases the contact area, which can better allow the reaction solution to contact the washing liquid, and the small molecule impurities in the reaction solution are better dissolved by the washing liquid; the small molecule impurities in the reaction solution may be wrapped by the macromolecular polymer, which can also promote the exposure of small molecule impurities and enter the washing liquid; the macromolecular polymer is dispersed and fully in contact with the washing liquid, and the precipitate formed by it will also be dispersed in the washing liquid, and the precipitation process will reduce the wrapping phenomenon of impurities.
[0082] Comparing Examples 1-4, it was unexpectedly found that the greater the voltage set by the electrospinning device, the smaller the PDI of the BARC resin and the greater the minimum molecular weight, indicating that the greater the voltage, the narrower the molecular weight distribution of the BARC resin. At the same time, the greater the voltage, the greater the weight average molecular weight. Therefore, within a certain range, a BARC resin with an ideal weight average molecular weight and molecular weight distribution can be obtained by adjusting the voltage.
[0083] Comparative Study on Application of BARC Resin
[0084] Take the BARC resin in each example, mix 2g of BARC resin, 1g of crosslinking agent, 0.1g of heated acid generator and 25g of solvent, and after fully dissolving, filter with 0.22 micron and 0.1 micron filters in turn to obtain a BARC mixture.
[0085] The BARC mixture was coated on a 12-inch silicon wafer at a speed of 1500 rpm, baked on a hot plate at 220°C for 60 seconds, washed with a thinner, and baked at 120°C for 60 seconds.
[0086] Add photoresist solution, apply at 1500 rpm, bake at 120℃ for 60s, and then expose to 193nm deep ultraviolet light. The exposure intensity is 10-59mj / cm 2 After exposure, the photoresist was baked on a hot plate at 120°C for 60 seconds, and finally developed in a 2.38wt% TMAH developer for 60 seconds, and then dried to obtain a 193nm deep ultraviolet photoresist. The photolithography results were detected using CD-SEM.
[0087] After BARC was applied, the film thickness and uniformity were tested with a film thickness meter. The results are shown in the following table:
[0088] Table 2 Film thickness results
[0089] Test items Speed / rpm PAB FT MEAN(A) STDEV(A) Example 1 1500 220C 60S 980 11.8 Example 2 1500 220C 60S 998 8.9 Example 3 1500 220C 60S 967 5.4 Example 4 1500 220C 60S 990 3.3 Comparative Example 1 1500 220C 60S 920 15.0 Comparative Example 2 1500 220C 60S 942 14.3 Comparative Example 3 1500 220C 60S 960 12.1
[0090] From the film thickness test results, if Figure 1 The photoresist film thickness of each BARC resin is not significantly different, indicating that the difference in weight average molecular weight and molecular weight distribution of BARC resin has little effect on the film thickness. Figure 2 The uniformity of the photoresist film thickness corresponding to the BARC resin of Examples 1-4 is significantly better than that of Comparative Examples 1-3, and the uniformity of Examples 1 to 4 shows a significant trend of improving, indicating that the weight-average molecular weight and molecular weight distribution of the BARC resin affect the uniformity of the photoresist film, and the narrower the molecular weight distribution of the BARC resin, the better the uniformity. By using the BARC resin of Examples 1-4 for the preparation of 193nm deep ultraviolet photoresist, a 193nm deep ultraviolet photoresist with better uniformity can be obtained.
[0091] like Figure 3 , which are the 193nm deep ultraviolet photoresist images corresponding to each example, and the corresponding LWR results are as follows:
[0092] Table 3 LWR results
[0093] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 LWR 7.4 7.1 6.5 6.4 8.9 9.1 9.0
[0094] Depend on Figure 3 As can be seen from the table above, compared with the comparative example, the photoresist patterns prepared by the BARC resins of Examples 1-4 are clearer and have smaller LWR, and the LWR corresponding to Examples 1-4 is on a downward trend, which is consistent with the molecular weight distribution and film thickness results of the BARC resin. This indicates that the narrower the molecular weight distribution of the BARC resin, the better the uniformity of the film thickness formed, and when preparing a 193nm deep ultraviolet photoresist, the LWR can be reduced to obtain a pattern with higher resolution.
[0095] In summary, the BARC resin preparation method of the present invention uses p-hydroxystyrene and methoxyethyl methacrylate as monomer raw materials, adds an initiator and performs a thermal polymerization reaction to obtain a polymer containing a benzene ring structure. Through an electrostatic spinning device, the mixed solution after the reaction is sprayed to form fine droplets, which enter the washing liquid for cleaning and precipitation, effectively removing small molecular impurities, separating the polymer, and finally obtaining the polymer, i.e., BARC resin, which is used as the main component of BARC, can make the film thickness uniformity of BARC better, thereby better eliminating the standing wave effect, so that a finer pattern is obtained under 193nm deep ultraviolet lithography, and is particularly suitable for 193nm deep ultraviolet photoresist preparation.
[0096] It is understandable that those skilled in the art can, under the guidance of the above embodiments, combine various implementation methods in the above embodiments to obtain technical solutions of multiple implementation methods.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a BARC resin, characterized in that: The method comprises: S1, placing styrene monomers and acrylic monomers in a reaction solvent and mixing them evenly to obtain a prepolymer solution; S2, adding an initiator to the prepolymer liquid, heating it to boiling to carry out a free radical polymerization reaction, and obtaining a reaction liquid; S3, adding the reaction liquid to the electrospinning device, and placing the needle outlet of the electrospinning device above the container filled with washing liquid; turning on the electrospinning device, pushing the reaction liquid, and when droplets appear on the needle, applying voltage to the needle to form a spray and enter the washing liquid, the small molecular substances in the spray are dissolved in the washing liquid, and the macromolecular substances form precipitation; S4, separating the precipitate to obtain the BARC resin.
2. The preparation method according to claim 1, characterized in that The styrene monomer is at least one of p-hydroxystyrene and styrene; the acrylic monomer is at least one of methoxyethyl methacrylate and hydroxypropyl methacrylate.
3. The preparation method according to claim 1, characterized in that: The reaction solvent is at least one of tetrahydrofuran, butanone, and propylene glycol methyl ether acetate.
4. The preparation method according to claim 1, characterized in that: The styrene monomer is p-hydroxystyrene; the acrylic monomers are methoxyethyl methacrylate and hydroxypropyl methacrylate; the reaction solvent is tetrahydrofuran; the weight ratio of p-hydroxystyrene, methoxyethyl methacrylate, hydroxypropyl methacrylate and tetrahydrofuran in the prepolymer solution is 1-10:1-10:1-10:12-120.
5. The preparation method according to claim 1, characterized in that: The initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile and azobisisoheptanenitrile.
6. The preparation method according to claim 1, characterized in that: The total amount of the styrene monomer and the acrylic monomer used and the amount of the initiator used are in a ratio of 10-100:0.06-0.
6.
7. The preparation method according to claim 1, characterized in that: The specification of the needle of the electrospinning device is 15G, the outer diameter is 1.8mm, the distance between the needle and the upper surface of the washing liquid is 15cm, the voltage applied to the needle ranges from 10 to 30kv, and the propulsion rate of the reaction liquid is 1mL / h.
8. The preparation method according to claim 1, characterized in that: The washing liquid is at least one of isopropanol, n-heptane, n-hexane and ethanol.
9. A BARC resin, characterized in that The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the BARC resin according to claim 9 in the preparation of 193 nm deep ultraviolet photoresist.
